Penentuan Rute Distribusi Produk yang Meminimumkan Jarak Tempuh dan Jumlah Kendaraan dengan Pendekatan Metode Heuristik Vehicle Routing Problem - Indrawati, Chatarina Dian (Widya Warta, 2014)
Distribution route and time management play important roles in a business. These aspects are closely concerned with the means of transportation and speed of delivery of a product. This research is an attempt at tracing the distribution process and time spending in the marketing of soybean tempe. It is a case study on â€œMurniâ€ SME production of Mantab Rasa. The study applied Heuristic method using constructive initial feasible Nearest to depot method with Vehicle Routing Problem Time Windows (VRPTW). The result found four routes for vehicle B (two-wheeled motorcycle) and one routes for vehicle A (three-wheeled mototrcycle). The total time spent was 252.775 minutes for the distance 41 miles.